Manuscript and Material Evidence for Janies Ussher's Authorship of A Body of Divinitie (1645) - Perkins, Harrison (The Evangelical quarterly, 2018)
James Ussher was one of the most important theologians in England and Ireland during the seventeenth century, with connections to both theology and politics. Perhaps the most influential theological work attributed to him has been A Body of Divinitie, a lengthy and detailed catechism that was very popular among his contemporaries. Yet, some scholars have disputed his authorship of this text. In this essay, I bring forward manuscript and material evidence to demonstrate Ussher's continual use of the content of the Body, and I consider the historical context that helped cause doubt about his authorship. This shows that the content legitimately belonged to Ussher.